PENGARUH NAUNGAN DAN LEVEL NITROGEN TERHADAP KARAKTER PERTUMBUHAN RUMPUT CORONIVA - Anis, S D.; Kaligis, D A; Dalie, S (ZOOTEC, 2015)
EFFECT OF SHADING AND NITROGEN LEVEL TO CHARACTER OF GROWTHÂ  CORONIVA GRASS (Brachiaria humidicola).The Coroniva grass (Brachiaria humidicola) or Schweick was ruminant animal feed grass with high ability for land recovering, land erosion and high nutrient quality for ruminant animals. In the areas with high sun light and land nutrient availability,this grass was capable to increase carbon accumulation under top soil and contribute the nitrogen (N) as fixation result of Azotobacter microorganism. Under shading areas and lack of land nutrient availability, especially nitrogen, growth and production potentials had not been fully explored. The objective of this study was to evaluate the levels of shading areas and nitrogen fertilizer on growth traits, dried matter plant leaf canopy and ratio between plant canopy and plan root of Coroniva grass (Brachiaria humidicola). Treatments were divided into three levels of shading (0%, 40%, 70%) and nitrogen fertilizer levels of 0 kg, 50 kg and 100 kg ha-1. Treatments were applied using factorial design based on block randomized design. Results showed that interaction between shading area of 40% and N level of 100 kg ha-1 produced the highest numbers and length of stolon, while the highest numbers of propagating plant were found at interaction between shading area of 40% and N level ofÂ  50 kg ha-1. Therefore, it can be concluded that growth traits of Coroniva grass were determined by the factors of shading areas and nitrogen macro element. Key word: Coroniva grass, shading area, nitrogen, growth.